1990
DOI: 10.1063/1.103844
|View full text |Cite
|
Sign up to set email alerts
|

Reversible modification of CdTe surface composition by excimer laser irradiation

Abstract: KrF excimer laser irradiation of CdTe at fluences below the melt threshold (≤75 mJ/cm2) removes surface layers and produces reversible changes in the surface composition that depend upon the laser fluence and number of laser pulses delivered to the surface. At fluences above ∼40 mJ/cm2 a Te-rich layer is obtained. A stoichiometric composition can be restored by irradiation at reduced laser fluence. The primary desorption products are Cd and Te2, and the velocities of these species are well described by a Maxwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…In this case, the power dependence of the dark current is observed at a relatively high temperature due to a lower concentration of charge carriers (~10 7 and 10 12 cm -3 at ambient temperature, respectively) as well as lower carrier mobility in Cd 0.9 Zn 0.1 Te as compared to nGe. The observed conversion of the conductivity type is not trivial, since it is generally accepted that laser irradiation results in formation of cadmium vacancies (stoichiometry violation) [7,15]. A possible reason for the observed conversion is generation of a large amount of dislocations and interstitial cadmium.…”
Section: Experimental Data and Discussionmentioning
confidence: 98%
“…In this case, the power dependence of the dark current is observed at a relatively high temperature due to a lower concentration of charge carriers (~10 7 and 10 12 cm -3 at ambient temperature, respectively) as well as lower carrier mobility in Cd 0.9 Zn 0.1 Te as compared to nGe. The observed conversion of the conductivity type is not trivial, since it is generally accepted that laser irradiation results in formation of cadmium vacancies (stoichiometry violation) [7,15]. A possible reason for the observed conversion is generation of a large amount of dislocations and interstitial cadmium.…”
Section: Experimental Data and Discussionmentioning
confidence: 98%
“…6 that a film of 100 nm absorbs 100% of the UV light and about 60% of the green one. To avoid direct ablation of the polycrystalline CdTe, the pulse energy was kept below 500 J. Ablation is out of the scope of this article but of course, we expect that the ablation threshold will be different to one reported by Brewer et al 4 for singlecrystal CdTe. The laser was placed about 2 m from the chamber; the beam was delivered by several mirrors and focused by a spherical quartz lens of 155 mm focal length.…”
Section: Methodsmentioning
confidence: 95%
“…The pulsed-laser irradiation localized to a microscopic area causes a transient temperature rise, enough to induce microreactions and in many cases even to melt the solid and evaporate atoms from the surface. [1][2][3][4] The induced local chemical and morphological changes of the near-surface region can affect the electronic properties and may be used for modifying surface band bending, surface recombination, and contact formation. 5 The most recent scanning tunneling microscopy ͑STM͒, transmission electron microscopy ͑TEM͒, and electron diffraction studies on the transformation of smooth CdTe thin films under UV laser irradiation in air have shown the appearance of hillocks, tentatively related to formation of a Cd metal phase as a result of photon-induced oxidation of the CdTe.…”
Section: Introductionmentioning
confidence: 99%
“…35 Brewer et al more fully explored the phenomenon using a KrF excimer laser with 15 ns pulses and showed that above a threshold fluence, a Te-rich surface was created before the onset of melting. 31 Furthermore, it was discovered that this behavior was completely reversible by the application of sub-threshold light, which suggested to the authors that the mechanisms responsible were a temperature-related competition between Cd and Te 2 desorption. A Te surface enrichment with ruby or KrF laser pulses has been experimentally confirmed by several other groups.…”
Section: Laser-induced Surface Modificationmentioning
confidence: 99%
“…30,31 When a pulsed UV laser is applied, the surface rapidly heats to very high temperatures causing slightly more Cd loss than Te. This can leave either a Te-rich surface, which effectively dopes the surface highly p-type due to the increased presence of Cd vacancy acceptors, or leaves a thin Te film, or some combination of both.…”
Section: Laser-induced Surface Modificationmentioning
confidence: 99%